Dynamics of Blister Actuation in Laser-Induced Forward Transfer for Contactless Microchip Transfer - DoYoung Kim; Seong Ryu; Sukang Bae; Min Wook Lee; Tae-Wook Kim; Jong-Seong Bae; Jiwon Park; Seoung-Ki Lee (Nanomaterials)
The rapid evolution of microelectronics and display technologies has driven the demand for advanced manufacturing techniques capable of precise, high-speed microchip transfer. As devices shrink in size and increase in complexity, scalable and contactless methods for microscale placement are essential. Laser-induced forward transfer (LIFT) has emerged as a transformative solution, offering the precision and adaptability required for next-generation applications such as micro-light-emitting diodes (μ-LEDs). This study optimizes the LIFT process for the precise transfer of silicon microchips designed to mimic μ-LEDs. Critical parameters, including laser energy density, laser pulse width, and dynamic release layer (DRL) thickness are systematically adjusted to ensure controlled blister formation, a key factor for successful material transfer. The DRL, a polyimide-based photoreactive layer, undergoes photothermal decomposition under 355 nm laser irradiation, creating localized pressure that propels microchips onto the receiver substrate in a contactless manner. Using advanced techniques such as three-dimensional profilometry, X-ray photoelectron spectroscopy, and ultrafast imaging, this study evaluates the rupture dynamics of the DRL and the velocity of microchips during transfer. Optimization of the DRL thickness to 1 µm and a transfer velocity of 20 m s⁻1 achieves a transfer yield of up to 97%, showcasing LIFT’s potential in μ-LED manufacturing and semiconductor production.